2012
DOI: 10.1007/s15010-012-0343-5
|View full text |Cite
|
Sign up to set email alerts
|

A stringent preemptive protocol reduces cytomegalovirus disease in the first 6 months after kidney transplantation

Abstract: Background The optimal strategy to prevent cytomegalovirus (CMV) disease after kidney transplantation continues to be open to debate. The preemptive approach requires regular determination of CMV viremia and prompt initiation of therapy. Methods We retrospectively compared the incidence of CMV disease during two periods at our center: A first phase (P1, n = 84 kidney recipients), during which time the intensity of surveillance was determined by the responsible physician, was compared to a second phase (P2, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…We found a similar incidence rate of CMV disease in KT (4.1/100 person-years) and HCT (5.0/100 person-years) patients during preemptive therapy. Separate previous studies of KT recipients or HCT recipients have reported rates of CMV disease after KT and HCT of 0.8% to 9.0% [7,8,22] and 5.8% [9], respectively. Our findings on the rates of CMV disease in KT and HCT recipients are in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We found a similar incidence rate of CMV disease in KT (4.1/100 person-years) and HCT (5.0/100 person-years) patients during preemptive therapy. Separate previous studies of KT recipients or HCT recipients have reported rates of CMV disease after KT and HCT of 0.8% to 9.0% [7,8,22] and 5.8% [9], respectively. Our findings on the rates of CMV disease in KT and HCT recipients are in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This can only be achieved by clear local guidelines and their strict implementation, as recently shown in our centre [26]. 2 Cost: clear statements concerning cost are difficult.…”
Section: A Critical View On Generalized Prophylaxismentioning
confidence: 97%
“…& When a preemptive therapy strategy is used, it is recommended that the center develop and validate their local protocol (167). Because preemptive therapy relies on laboratory monitoring, it is important that an appropriate threshold value be chosen for the specific assay that is used.…”
Section: Preemptive Therapy Strategymentioning
confidence: 99%